Implementation of Storytelling Method with Folktales in Instilling Character Values in Children: A Study at ABA Warungboto Kindergarten - Adwiah, Amalia Rabiatul; Aulia Faraz Tantia; Intan Asyikin Rantikasari (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study aims to see how the implementation of the storytelling method using folklore in instilling character values in children at TK ABA Warungboto. This study used a descriptive qualitative approach to analyze the data obtained through interviews, observations, and documentation involving 15 children from Class B as research subjects. The research results indicate that storytelling methods significantly enhance children's enthusiasm and learning motivation, with noticeable improvements in their attitudes, honesty, responsibility, and independence. Furthermore, this study found that supporting tools such as puppets and storybooks can reinforce the impact of this method in instilling these values. However, this research has limitations as it only focuses on one school and the use of folklore as the sole medium. Practical implications include increasing storytelling methods in character education, emphasizing diversifying stories, and employing interactive media. This study also recommends routine evaluations to measure the effectiveness of this approach. In conclusion, storytelling methods hold great potential in character education at the kindergarten level, and the findings of this research can serve as inspiration for character education in other schools.